Electronic Student Activity Sheet Integrated with Augmented Reality for Training Visual-Spatial Intelligence in Molecular Shapes - Putri Dela Permatasari; Kusumawati Dwiningsih; Noviansyah Kusmahardhika (Jurnal Pendidikan Sains Indonesia, 2026)
Molecular structure material discusses the spatial arrangement of atoms in a molecule and is abstract in nature, often making it difficult for students to understand. This difficulty is also caused by students' inability to visualize molecules. Spatial visual intelligence plays an important role in learning abstract chemistry concepts because it helps students understand shapes and structures through pictures, diagrams, or 3D models. One effective way to train this intelligence is by using technology-based learning media. Augmented Reality technology is one innovation that allows students to interact with abstract material. The research method used was Research and Development (RnD) with a 4D model (Define, Design, Development, Disseminate), but modified to the Development stage. In the Design stage, an augmented reality prototype was developed using Assemblr Edu software to create molecules in 3D form. The research subjects were 21 grade XI students at IPIEMS High School in Surabaya. The research results showed that the augmented reality-integrated E-LAPD was declared valid with a median score of ≥ 4 on content and construct validity. Student response questionnaires obtained a score of 95.53%, and observations of student activities reached 97.33%, both categorized as very practical. The effectiveness of LAPD was demonstrated by a significant difference between the pretest and posttest scores for students' visual-spatial intelligence and an effectiveness score with an N-Gain of 0.66 (moderate category). Thus, the developed product is suitable for training students' visual-spatial intelligence in chemical molecular structures